Antiviral activity of astragaloside II, astragaloside III and astragaloside IV compounds against dengue virus: Computational docking and in vitro studies. (March 2021) - Indu, Purushothaman; Arunagirinathan, Narasingam; Rameshkumar, Marimuthu Ragavan; Sangeetha, Kodhandan; Divyadarshini, Angamuthu; Rajarajan, Swaminathan
Abstract: This study was aimed to identify the phytocompounds possessing anti-dengue virus activity using in silico and in vitro approaches. A total of 7000 phytocompounds were virtually screened against protein targets (envelope, NS2b/NS3, and NS5) of dengue virus using iGEMDOCK and individually docked using Maestro 10.7 module of Schrödinger software. In vitro cytotoxicity and antiviral studies were performed using vero cell line. Finally, three phytocompounds namely astragaloside II, astragaloside III, and astragaloside IV were screened based on their highest binding energy values against protein targets. Astragaloside III exhibited the highest interaction energy value of −8.718 kcal/mol and −8.447 kcal/mol against envelope, and NS2b/NS3 targets, respectively. Astragaloside IV exhibited −7.244 kcal/mol against SAM site, and −9.179 kcal/mol against RNA cap site of NS5 targets. In silico ADMET analysis revealed that astragaloside II, III, and IV were non-mutagenic and non-carcinogenic in nature and these compounds were also non-toxic to vero cells upto 1000 μg/mL. Against dengue virus serotype 3, astragaloside II exhibited substantial antiviral activity at the concentration of 1.56 μg/mL followed by astragaloside III at 6.25 μg/mL and astragaloside IV at 12.5 μg/mL. Also, against dengue serotype 1, astragaloside II showed the maximum antiviral activity at 1.56 μg/mL followed by astragaloside III and IV at 3.125 μg/mL. This study concludes that astragaloside II, III, and IV compounds had potential in vitro anti-dengue virus activity. Graphical abstract: Image 1 Highlights: 7000 phytocompounds were virtually screened against protein targets of dengue virus include envelope, NS2b/NS3, and NS5. Astragaloside II, III and IV were screened based on their high interaction energy values against dengue virus protein targets. Against dengue virus serotype III, astragaloside II exhibited substantial antiviral activity at the concentration of 1.56µg/ml. Against dengue virus serotype I, astragaloside II exhibited substantial antiviral activity at the concentration of 1.56 µg/ml.